THE EFFECT OF TEMPERATURE ON Na, K, AND Ca EMISSION DURING COMBUSTION OF PINEWOOD SAWDUST - Legonda, Isack (Universitas Negeri Surabaya, 2024)
Quantification of Na, K, and Ca emissions from the combustion of pinewood sawdust has been conducted. The concentration of these metals in both sawdust and ashes was determined using inductive coupled plasma spectrometry. Ash samples were collected at 550 oC and 900 oC to simulate the actual operating conditions for thermal conversion processes which are mainly pyrolysis, gasification, and combustion. Also, tar samples were collected from the pyrolysis process conducted at 500 oC to assess the concentration of selected metals. The analysis results showed that emissions of Na, K, and Ca were found to range from 19-39 ppm, 340-400 ppm, and 500-550 ppm for temperatures between 550 oC and 900 oC respectively. The presence of metal content in tar supports that the emission mechanism can be through adhesion during the volatilization of heavy hydrocarbons from biomass combustion. Thus, the study findings suggest that treatment of metal emissions from the open fire such as that of firewood cookstoves is highly recommended.